2019
DOI: 10.3390/catal9020202
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical ZSM-5 Zeolite with Enhanced Catalytic Activity for Alkylation of Phenol with Tert-Butanol

Abstract: Using polyethylene glycol as a mesoporous soft template, a series of hierarchically porous ZSM-5 zeolites were prepared. X-ray diffraction, infrared spectroscopy, N2 adsorption–desorption, and transmission electron microscopy results demonstrated that the resultant materials contained a micro–mesoporous structure. Since the existence of mesoporous structure favors the diffusion of large molecular reactants and products, the phenol conversion and selectivity to 2,4-Di-TBP on the hierarchical ZSM-5 zeolite can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…PDDA-Cl (polidialydimethyl ammonium chloride) aims to build this hierarchical ZSM-5 material so that the microporous and mesoporous material is formed in one structure. This results is different from the typical curve for microporous ZSM-5 isotherms which usually shows that specific surface area is developed from micropores [27], but it is consistent with the curve reported by Xu et al [26] for hierarchical zeolites containing micro-and mesopores in one structure. In addition, the average diameter of the pores formed were 1.8842 nm and 2.7419 nm, which are within the range for microporous (d < 2 nm) and mesoporous (2 nm < d < 50 nm), respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 70%
See 1 more Smart Citation
“…PDDA-Cl (polidialydimethyl ammonium chloride) aims to build this hierarchical ZSM-5 material so that the microporous and mesoporous material is formed in one structure. This results is different from the typical curve for microporous ZSM-5 isotherms which usually shows that specific surface area is developed from micropores [27], but it is consistent with the curve reported by Xu et al [26] for hierarchical zeolites containing micro-and mesopores in one structure. In addition, the average diameter of the pores formed were 1.8842 nm and 2.7419 nm, which are within the range for microporous (d < 2 nm) and mesoporous (2 nm < d < 50 nm), respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 70%
“…The results showed that the surface area of the as-synthesized hierarchical ZSM-5 zeolite was 348.6 m 2 /g. This property is important, because the greater the surface area, the easier it is to disperse metal oxides as active sites on the support surface [26]. Furthermore, Figure 5 shows the characteristic isotherm curves (type IV), which indicates a mesoporous structure.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…32,33,34 In that context of emergence of new zeolitetype materials such as hierarchical zeolites it appears very important to identify the influence of the morphology on the formation and evolution of CSS. 25,35,36,37,38 MFI-type zeolite is particularly interesting due to its three-dimensional channel system with 10-membered ring (MR) openings (0.55-0.56 nm). Thanks to new synthesis methods, [27][28][29][30][39][40][41][42][43] it is now possible to control the morphology of zeolites to eventually make their properties "tunable" not only by preparing materials in the form of microcrystals but also with more complex architectures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pore walls of the mesoporous materials were amorphous, and the acidity of the materials was relatively low. Therefore, mesoporous materials had poor catalytic activity in acid-catalyzed reactions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These methods need be completed in at least two steps, so the preparation methods were more complicated. In our previous work, we used polyethylene glycol as the mesoporous soft template to synthesize hierarchical ZSM-5 zeolites [21]. However, there were two kinds of acid sites, which would result in side reactions.…”
Section: Introductionmentioning
confidence: 99%